The Anthropologist as Audience: Engaged Listening among Khmer Rouge Survivors and Ukrainian War Refugees (Medicine Anthropology Theory, 2023)
Although the Khmer Rouge regime was responsible for the deaths of roughly 2.2 million Cambodians—and the persecution and abuse of millions more—only a handful of survivors have been able to testify at the tribunal established to prosecute former leaders of the regime. Partly to address this gap, an NGO affiliated with the tribunal has been offering ‘Testimonial Therapy’ for the past decade as a form of reparation for survivors with symptoms of psychological distress. For 16 months, I followed survivors undergoing this therapy, during which they developed a testimonial narrative of their life story in collaboration with a local mental health worker. In this Position Piece, I consider Myers’ conception of ‘moral agency’ (2015) in relation to this process of personal narrative creation, and the critical importance of audience engagement. I then reflect on my own positionality as both ethnographer and active listener, tracing how this affective posture has been formed not only through fieldwork, but also through engagement with family narratives of loss in the context of war-torn Ukraine.